homework 5 solution

homework 5 solution - 640:527: Homework 5: Solutions 1....

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 640:527: Homework 5: Solutions 1. Greenberg 4.6, # 1. Let y = a n x r + n . Then y = ( r + n ) a n x r + n- 1 and y 00 = ( r + n )( r + n- 1) x r + n- 2 . Plugging these into Bessels equation x 2 y 00 + xy + ( x 2- 2 ) y = 0 gives 0 = X ( r + n )( r + n- 1) x r + n + X ( r + n ) a n x r + n- X 2 a n x r + n + X a n x r + n +2 = X ( r + n )( r + n- 1) + ( r + n )- 2 x r + n + X a n x r + n +2 . Notice that a n x r + n +2 = 2 a n- 2 x r + n , and that ( r + n )( r + n- 1) + ( r + n ) = ( r + n ) 2 . Thus 0 = X ( r + n ) 2- 2 x r + n + X 2 a n- 2 x r + n = r 2- 2 a x r + ( r + 1) 2- 2 a 1 x r +1 + X 2 ( ( r + n ) 2- 2 ) a n + a n- 2 x r + n . This is essentially equation (3) of the text. I have just written out the first two terms of the series. Greenberg 4.6, # 2. Before starting this problem we make a general remark. Suppose 1 , 2 ,... is a given sequence. Suppose now we want to find the solution b ,b 1 ,b 2 ,... to the recursion equation b k = k b k- 1 , k 1 , and b = B. (1) The solution is given by the formula b k = k k- 1 k- 2 1 b , b = B. (2) It is easy to see why this is true. Start with (1) and then apply the formula with k- 1 instead of k to express b k- 1 in terms of b k- 2 : b k = k b k- 1 = k ( k- 1 b k- 2 ). Repeat this process k times: b k = k k- 1 k- 2 b k- 3 = = k k- 1 k- 2 1 b . The problem is to solve the Bessel equation of order = 1 / 2. This is the equation x 2 y 00 + xy + ( x 2- (1 / 4)) y = 0. We look for a solution of the form y = a n x r + n . The indicial equation recursion equation may be obtained by substituting = 1 / 2 into equation (3a) of section 4.6 in the text, and the result is r 2- (1 / 4) a = 0. Since a 6 = 0, it follows that r 2- 1 / 4 = 0. This has the roots r 1 =- 1 / 2 and r 2 = 1 / 2. These roots differ by an integer and there might be a problem, but we know there is always a solution of the form y = a n x r + n when r equals the larger root. So first we work out this solution and take r = r 2 = 1 / 2. The recursion equations for this choice of r can be obtained by substituting r = 1 / 2 and = 1 / 2 in equations (3b) and (3c) of the text. (I am using n as an index, rather than k .) We get (1 + 1 / 2) 2- 1 2 a 1 = (5 / 4) a 1 = 0 (3) ( n + 1 / 2) 2- (1 / 4) a n + a n- 2 = ( n +1) na n + a n- 2 = 0 , n 2 . (4) The first equation implies that a 1 = 0. The second equation gives the recursion a n =- a n- 2 ( n + 1) n . (5) 1 By setting n = 3, a 3 =- a 1 / 12 = 0, a 5 =- a 3 / 30 = 0. Continuing, it is clear that a n = 0 for all odd n . For even n , we derive a recursion by replacing n in (5) by 2 k ....
View Full Document

Page1 / 6

homework 5 solution - 640:527: Homework 5: Solutions 1....

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online